High-Performance Hybrid Supercapacitor Based on Graphene-Wrapped Mesoporous T-Nb2O5 Nanospheres Anode and Mesoporous Carbon-Coated Graphene Cathode - Ma, Guoqiang; Li, Ke; Li, Yuanyuan; Gao, Biao; Ding, Tianpeng; Zhong, Qize; Su, Jun; Gong, Li; Chen, Jian; Yuan, Longyan; Hu, Bin; Zhou, Jun; et al. (ChemElectroChem, 2016)
Lithium‐ion hybrid supercapacitors combining the advantages of Li‐ion batteries and supercapacitors have been the subject of extensive interest in the field of energy storage because of their high energy density at high power density. Herein, we report reduced graphene oxide (rGO) cross‐linked mesoporous T‐Nb2O5 nanospheres (T‐Nb2O5 MNSs/rGO) as high‐performance Li+ intercalation pseudocapacitive material and mesoporous carbon‐coated rGO (MC/rGO) as high‐power electric double‐layer capacitive material. The T‐Nb2O5 MNSs/rGO anode material boasts a high reversible capacity of 181 mAh g−1 at a current density of 20 mA g−1, good cycle stability, with 85 % capacity retention after 1000 cycles, as well as excellent rate capability. The MC/rGO cathode material delivers a large capacity of 110 and 86 F g−1 at a current density of 500 and 10 000 mA g−1 in organic electrolyte in the voltage range of 3–4.5 V (vs. Li/Li+). The advanced Li‐HSCs with a T‐Nb2O5 MNSs/rGO anode combined with a MC/rGO cathode show the highest power density of 25 600 W kg−1 at 21 Wh kg−1, which is much higher than that of similar Li‐HSC systems previously reported. Furthermore, the Li‐HSCs exhibit an excellent cyclability, with 82 % capacitance retention after 4000 cycles. Best of both: Nonaqueous high‐performance lithium‐ion hybrid supercapacitors (Li‐HSCs) are fabricated by using reduced graphene oxide cross‐linked mesoporous T‐Nb2O5 nanospheres (T‐Nb2O5 MNSs/rGO) as Li+ intercalation pseudocapacitive material and mesoporous carbon‐coated rGO as electric double‐layer capacitive material. The Li‐HSC exhibits a high energy density of 56 Wh kg−1, a power density of 25 600 W kg−1, as well as excellent cycling stability.